2022
DOI: 10.1002/cre2.550
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intralesional injections of platelet‐rich plasma in patients with oral lichen planus: A pilot randomized clinical trial

Abstract: Objective: To evaluate the clinical efficacy of intralesional platelet-rich plasma (PRP) injections compared to intralesional triamcinolone acetonide (TA) injections in the treatment of erosive oral lichen planus (EOLP).Material and Methods: Twenty patients with EOLP were assigned randomly to either PRP or TA group. Patients received weekly intralesional injections for 4 weeks, and then followed up for 3 months on regular visits every 2 weeks. Pain scores using numerical pain score and clinical score were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… 36 Likewise, intralesional PRP injections in cases with recalcitrant erosive OLP for 4–8 weeks showed a significant reduction in pain, ulcer size, and erythema. 37 , 38 , 39 , 40 , 41 In addition, a randomized clinical trial showed that PRF injections in OLP resulted in a significant reduction of lesion size, pain score, and decreased mean values of oral health impact profile scale, which were comparable to corticosteroid injections. 42 , 43 , 44 Overall, clinical studies suggest that applying PCs either topically or intralesional for an average of eight weeks would be a valid treatment option for recalcitrant OLP lesions.…”
Section: Clinical Application Of Pc In Chronic Oral Mucosal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 Likewise, intralesional PRP injections in cases with recalcitrant erosive OLP for 4–8 weeks showed a significant reduction in pain, ulcer size, and erythema. 37 , 38 , 39 , 40 , 41 In addition, a randomized clinical trial showed that PRF injections in OLP resulted in a significant reduction of lesion size, pain score, and decreased mean values of oral health impact profile scale, which were comparable to corticosteroid injections. 42 , 43 , 44 Overall, clinical studies suggest that applying PCs either topically or intralesional for an average of eight weeks would be a valid treatment option for recalcitrant OLP lesions.…”
Section: Clinical Application Of Pc In Chronic Oral Mucosal Diseasesmentioning
confidence: 99%
“… Lesion Type of PCs Effect of PCs Ref. Oral lichen planus PRF membrane PRF resulted in a decrease in lesions' size within 3 weeks of treatment 36 Platelet solution PC improved quality of life and decreased pain 35 PRP Complete regression of the lesion after 4 weeks 41 PRP 90% of patients reported complete resolution of erythema 40 PRP Significant reduction in pain, size of the lesion and inflammation 37 i-PRF i-PRF reduced the lesion size by 59.8% and reduced the VAS scores by 47.6% 65 i-PRF i-PRF reduced pain and lesion's size 44 PRP PRP reduced pain and size of the ulcers 39 i-PRF i-PRF reduced VAS scores and lesion size by 68.5% and 74%, respectively 42 PRP Significant decrease in lesion size and pain score 38 Oral mucositis Platelet lysate Healing was good-to-complete in 5 out of 7 cases 50 Platelet gel Platelet gel resulted in improvement of oral mucosa, revealing restitutio ad integrum 46 Platelet gel PC resulted in improved quality of life and pa...…”
Section: Clinical Application Of Pc In Chronic Oral Mucosal Diseasesmentioning
confidence: 99%
“…Four clinical trials [ 14 , 20 , 22 , 24 ] were conducted to compare the improvement of clinical symptoms between blood derivatives and steroid treatment groups. However, the mean difference between the two groups was found to be(MD = -0.21 95% CI: -0.55 to 0.13), indicating no significant difference as shown (see Fig.…”
Section: Effects Of Interventionsmentioning
confidence: 99%
“…[ 2 6 7 ] Different energy-based therapies (low-level laser light, lasers, photodynamic therapy)[ 8 ] and biologics[ 6 ] have also been tried. Bioactives such as platelet-rich plasma (PRP)[ 9 ] and novel plant-derived therapies[ 10 ] offer newer adjuvant safer treatment options that can help avoid side effects associated with prolonged use of immunosuppressants.…”
Section: Introductionmentioning
confidence: 99%
“…A number of novel pharmacologic and non-pharmacologic treatments have been tried and reported as efficacious in few or small number of patients as an alternative to existing immunosuppressive and immunomodulatory agents anecdotally. They include photodynamic therapy, low-level light[ 132 ], lasers,[ 8 ] biomolecules such as platelet-rich plasma[ 9 ], topical thalidomide, topical hyaluronic acid, piperine derived from black pepper, aloe vera gel, topical and oral curcuminoids,[ 10 ] zinc (oral and topical), selenium, and probiotics. [ 133 ] Randomized controlled trials involving large number of patients and for longer duration are needed to establish an evidence-based role for these modalities in treating LP in its myriad manifestations.…”
Section: Introductionmentioning
confidence: 99%